Application of Gedog Weaving in the Design of Women's Work Clothing Ethnic Style - Soelistyowati, Soelistyowati (Jurnal Multidisiplin Indonesia, 2025)
Gedog weaving in Tuban faces challenges in the modern era, with traditional fabrics often less favored by younger generations, seen as irrelevant to contemporary lifestyles and work settings. Despite this, Gedog woven fabrics hold significant potential for development into diverse fashion products. This research explores this potential by designing a women's workwear collection that merges the beauty of Gedog motifs with modern designs. The goal is to create workwear that is aesthetic, functional, and comfortable for both work and formal occasions, boosting wearer confidence. The research employs qualitative methods, including descriptive analysis. Primary data was gathered through in-depth interviews with Gedog artisans, career women, and fashion industry experts to understand trends, while secondary data was obtained from literature studies. The creative process involved observing and exploring design elements, developing conceptual designs, and crafting moodboards and early sketches embodying ethnic-style workwear. The resulting designs are well-received by career women and cultural enthusiasts, demonstrating Gedog weaving's potential to enhance appreciation for local heritage. This initiative highlights the importance of collaboration between artisans, designers, and industry players in fostering innovation and sustainability for traditional wastra. By integrating Gedog motifs into contemporary fashion, the research supports the creative industry and provides opportunities for wastra artisans to reach broader markets. Ultimately, this effort emphasizes the preservation of traditional fabric culture in the globalization era, showcasing how cultural heritage can inspire innovative, sustainable fashion solutions.